The Influence of Financial Literacy on Family Financial Planning and Management Among Housewives - Nersa; Goso; Duriani (LP2M IAIN Palopo, 2025)
Financial literacy has an important role in family financial planning and management, especially among housewives who are responsible for managing family finances. This study aims to analyze the influence of financial literacy on family financial planning and management among housewives. Using a quantitative survey method, data was collected through the distribution of questionnaires to 211 housewife respondents in Tede Hamlet, and analyzed using linear regression. The results of the study show that the level of financial literacy has a significant and positive effect on the ability of housewives to prepare budgets, manage income and expenses, and make wise financial decisions. These findings confirm the importance of financial literacy education for housewives to improve family welfare.